Amélie Nothomb: a sulfuric hygiene of contemporary french literature - Jorge, Verónica Galíndez (Lettres Françaises, 2009)
This text aims at introducing Brazilian readers to Amélie Nothomb’s works, one of the most successful French language writers within the French editorial market. I shall quickly present some relevant biographical data and present my fi rst considerations regarding the relation of her writings to the history of French literature and writing in general.